2019
DOI: 10.1021/acs.accounts.9b00136
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicines for Reactive Oxygen Species Mediated Approach: An Emerging Paradigm for Cancer Treatment

Abstract: Conspectus Growth in the knowledge of cancer biology has led to the emergence and evolution of cancer nanomedicines by providing the rationale for leveraging nanotechnology to develop better treatment options. The discovery of nanometer-sized intercellular openings in the defective angiogenic tumor vasculature contributed to the development of an idea for the well-known cancer passive targeting regime, enhanced permeability and retention (EPR) effect, of the nanomedicines. Recently, reactive oxygen species (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
155
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(157 citation statements)
references
References 53 publications
1
155
0
1
Order By: Relevance
“…Chakraborty and Dass et al synthesized a series of 4-tert-butylbenzenethiolate (TBBT)-protected Au NCs and analyzed the ORR activity of Au NCs supported on single-walled carbon nanotubes. 51 The study on the reaction rate revealed that the ORR activity increases in the order of Au 36 (TBBT) 24 > Au 133 (TBBT) 52 > Au 279 (TBBT) 84 > Au 28 (TBBT) 20 (Fig. 8C and D).…”
Section: Electrocatalytic Application For Fuel Cellsmentioning
confidence: 92%
“…Chakraborty and Dass et al synthesized a series of 4-tert-butylbenzenethiolate (TBBT)-protected Au NCs and analyzed the ORR activity of Au NCs supported on single-walled carbon nanotubes. 51 The study on the reaction rate revealed that the ORR activity increases in the order of Au 36 (TBBT) 24 > Au 133 (TBBT) 52 > Au 279 (TBBT) 84 > Au 28 (TBBT) 20 (Fig. 8C and D).…”
Section: Electrocatalytic Application For Fuel Cellsmentioning
confidence: 92%
“…As we all know, the intratumor microenvironment is significantly hypoxic because tumors grow in an exaggerated way with insufficient O 2 supply. Accurate hypoxia imaging will allow clinicians to find and position those hypoxic tumors, contributing greatly to the cancer diagnosis and treatment . Early in 2009, Zhang and co‐workers designed and synthesized a kind of dual‐emissive materials, which contained an iodide‐substituted difluoroboron dibenzoyl methane‐poly (lactic acid), for hypoxia imaging in vivo.…”
Section: Rtp Materials In Biomedical Applicationsmentioning
confidence: 99%
“…Accurate hypoxia imaging will allow clinicians to find and position those hypoxic tumors, contributing greatly to the cancer diagnosis and treatment. [55] Early in 2009, Zhang and co-workers [56] designed and synthesized a kind of dual-emissive materials, which contained an iodide-substituted difluoroboron dibenzoyl methane-poly (lactic acid), for hypoxia imaging in vivo. They (Figure 5a).…”
Section: Bioimagingmentioning
confidence: 99%
“…Besides ROS-scavenging inorganic nanoparticles, organic nanoparticles with intrinsic antioxidant activities have been emerging as a potential platform for the treatment of numerous diseases associated with inflammatory disorders (Kim K. S. et al, 2015;Zhu and Su, 2017;Kwon et al, 2019). Several types of organic nanoparticles have shown higher antioxidative advantages over conventional antioxidants and radical scavengers, owing to their predominant properties in terms of pharmacokinetics, biodistribution, delivery efficiency, and robust scavenging capabilities of multiple radicals Ferreira et al, 2018;Ye et al, 2019;Zafar et al, 2019).…”
Section: Organic Nanoparticles With Intrinsic Antioxidant Activitiesmentioning
confidence: 99%